Pengaruh Pelaksanaan Ibadah Haji dan Umroh terhadap Transformasi Spiritual Jamaah di Kelompok Bimbingan Haji & Umroh Al Fatwa - Achmad Said; Wakib Kurniawan; Supriyatmoko Supriyatmoko (STIKes Ibnu Sina Ajibarang, 2025)
This research aims to analyze the influence of the Hajj and Umrah pilgrimages on the spiritual transformation of pilgrims. This research aims to analyze the influence of the Hajj and Umrah pilgrimages on the spiritual transformation of the congregation. Qualitative research methods with a phenomenological approach were used to collect and analyze data from 20 respondents from Hajj and Umrah pilgrims in the Al Fatwa Hajj & Umrah Guidance group. Qualitative research methods with a phenomenological approach were used to collect and analyze data from 20 respondents from Hajj and Umrah pilgrims who took part in guidance in the Al Fatwa Hajj & Umrah group. The research results showed that 90% of respondents experienced increased spiritual awareness, while 85% experienced positive behavioral changes, such as increased patience and honesty. As many as 80% of respondents reported deep spiritual experiences during worship, and 75% increased their involvement in religious activities after following guidance. Factors that influence this spiritual transformation include the quality of spiritual guidance, self-awareness, spiritual environment, and deep worship experiences. These findings contribute to a better understanding of the role of the Hajj and Umrah pilgrimages in forming the character and spirituality of the people, as well as the importance of effective guidance in this process.